ANALISIS KAUSALITAS KRIMINALITAS, PENDIDIKAN DAN KEMISKINAN DI INDONESIA - Nadya Centia Sari; Zul Azhar (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to examine the causality of crime, education and poverty in Indonesia. The data used is panel data during the period 2013-2017, with the technique of collecting documentation data and library studies obtained from relevant institutions and agencies. The variables used are Crime (Y1), Education (Y2), Poverty (Y3). The research methods used are: Granger Causality Test Panel and Vector Autoregression (PVAR) Panel. This study found that crime does not have a causal relationship to education, and vice versa. Crime does not have a causal relationship to poverty and vice versa. And poverty has a one-way relationship to education. The results of the PVAR found that crime in a given  year period was significantly influenced by crime in the previous period. Likewise, it was also with education and poverty.